2002
DOI: 10.2514/2.3877
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Repeatability of an Elastically Folded Composite Hinge for Deployed Spacecraft Optics

Abstract: A new type of folded composite hinge is investigated for its use in precision deployable spacecraft structures. The hinge is an integral feature of a composite tube intended for use as a structural truss member. The design of the hinge allows the tube to be elastically folded for stowage even with tube wall thicknesses from 0.4 to 1.7 mm. Whether the large but primarily elastic folding stresses impart permanent deformations to the tube after it is deployed is experimentally assessed. The data show that any suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 9 publications
(4 reference statements)
0
13
0
Order By: Relevance
“…The phased-array feed panels are attached to and deploy along with the main support truss. Each section of phased-array panels is connected by a composite hinge [33]. These composite hinges, also called strain-energy hinges, were also used in the main truss's folding longeron elements.…”
Section: Operationmentioning
confidence: 99%
“…The phased-array feed panels are attached to and deploy along with the main support truss. Each section of phased-array panels is connected by a composite hinge [33]. These composite hinges, also called strain-energy hinges, were also used in the main truss's folding longeron elements.…”
Section: Operationmentioning
confidence: 99%
“…For example, the initial deployment anomaly of the composite booms forming the antennas of the Mars Express Spacecraft was attributed to the loss of deployment moment after long term stowage [5,6]. Related experimental studies found that the deployed shape precision and vibration characteristics are also aected by time and temperature eects [7,8]. As deployable space structures are stowed for extended periods and subjected to varying temperature environments, viscoelastic eects need to be considered for designing deployable structures with predictable deployment behavior and nal shape precision.…”
Section: Introductionmentioning
confidence: 99%
“…A number of deployable space structure architectures have been or are currently under development, which employ thin composite laminates [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], two of which are shown in Fig. 1 [18,19].…”
mentioning
confidence: 99%